THE ROLE OF RAISING THE SPIRITUALITY OF THE PEOPLE IN ENLIGHTENMENTAL MOVEMENTS (American Journal of Interdisciplinary Research and Development, 2026)
The article reflects the emergence of the Jadid movement, along with the historical conditions under which the Jadid movement emerged, and the elevation of people’s spirituality within the framework of the influence of enlightenment and educational views that awakened in the last quarter of the 19th century and the beginning of the 20th century.